The Role of the Professional Specialization of the Auditor in Improving the Level of Disclosure in the Financial Reports - حمد رياض حبيب محمد; زاقوب علي عوض (Scientific Journal of University of Benghazi, 2023)
The aim of this study is to identify the importance of the auditor's professional specialization in auditing a specific activity or sector, as well as to identify its role and contribution to improving the level of disclosure in financial reports. To achieve these aims, the study adopted the deductive-inductive approach, and used an electronic questionnaire addressed to (86) Libyan auditors. The questionnaires were analyzed using descriptive statistical analysis. The study concluded that there is importance to the professional specialization of the auditor in a specific activity or sector, and that the professional specialization of the auditor contributes to improving the level of disclosure in the financial reports from the point of view of the Libyan auditors.. The study recommended conducting more studies on the importance of specialization in order to highlight the important role it plays in supporting the auditing profession by raising the knowledge level of auditors, and for the Libyan syndicate of Libyan Auditors and Accountants, in coordination with government agencies, to set rules and standards that regulate the auditing profession in the Libyan state in accordance with the development in global economies, which contributes to improving the quality of work submitted by practitioners of this profession. The study also recommended the auditors to adopt a strategy of professional specialization in their work, which reflects positively on the quality of the audit process. This study was limited to knowing the role of professional specialization in improving the level of disclosure in financial reports.